2019
DOI: 10.3390/d11090151
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Orthologs Derived from Whole Genome Sequencing Indicate Cryptic Diversity in the Bemisia tabaci (Insecta: Aleyrodidae) Complex of Whiteflies

Abstract: The Bemisia tabaci complex of whiteflies contains globally important pests thought to contain cryptic species corresponding to geographically structured phylogenetic clades. Although mostly morphologically indistinguishable, differences have been shown to exist among populations in behavior, plant virus vector capacity, ability to hybridize, and DNA sequence divergence. These differences allow for certain populations to become invasive and cause great economic damage in a monoculture setting. Although high mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 99 publications
2
42
1
Order By: Relevance
“…A study has demonstrated that NUMTs Insects 2020, 11, 58 9 of 15 were the cause for the incorrect identification of a putative Bemisia species that was given the name MEAM2 based on mtDNA COI data [87]. Another study using whole genome nuclear markers on the major clades of B. tabaci revealed the existence of fewer putative species (five so far), as opposed to the much larger number reported with mtCO1 [73]. In this study, B. tabaci Indian Ocean were collected from sweet potato and tomato, and their sequences were most closely related to Reunion 1 from Spain [88], although B. tabaci Indian Ocean has also been widely reported from sub-Saharan Africa and the surrounding islands [60,65,89].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has demonstrated that NUMTs Insects 2020, 11, 58 9 of 15 were the cause for the incorrect identification of a putative Bemisia species that was given the name MEAM2 based on mtDNA COI data [87]. Another study using whole genome nuclear markers on the major clades of B. tabaci revealed the existence of fewer putative species (five so far), as opposed to the much larger number reported with mtCO1 [73]. In this study, B. tabaci Indian Ocean were collected from sweet potato and tomato, and their sequences were most closely related to Reunion 1 from Spain [88], although B. tabaci Indian Ocean has also been widely reported from sub-Saharan Africa and the surrounding islands [60,65,89].…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite markers have also been developed and used to study B. tabaci populations [69,70]. Recent advances have utilized SNP genotyping and nuclear genes [71][72][73]. The mitochodrial DNA cytochrome oxidase I (mtCOI) marker has been the most widely used marker for phylogenetic studies of B. tabaci.…”
mentioning
confidence: 99%
“…The whitefly B. tabaci collected in the Punjab province of Pakistan were identified as mitotypes Asia II‐1, ‐5, and ‐7 (Dinsdale et al, ), which belong to the Asia II major clade of B. tabaci (Brown et al, ; de Moya et al, ). Characterization of the endosymbiont communities associated with endemic B. tabaci , with respect to composition, distribution, and ecological microniche(s) within of the Punjab district, suggests that certain mitotype–endosymbiont communities may have been/be selectively associated with previous and current outbreaks of cotton leaf curl disease, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The whitefly B. tabaci collected in the Punjab province of Pakistan were identified as mitotypes Asia II-1, -5, and -7 (Dinsdale et al, 2010), which belong to the Asia II major clade of B. tabaci (Brown et al, 2010;de Moya et al, 2019) (Zubair et al, 2017). Based on complex multitrophic interactions involving different plant host-virome-mitotype vector combinations, the endosymbiont community is hypothesized to contribute to niche-specific adaptation of B. tabaci mitotypes in the urban-and agroecosystems, the latter pronouncedly influenced by cropping and pesticide use regimes (see references in Bedford et al, 1994;Brown & Czosnek, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation